Butt or face? : super gross butts - Lavelle, Kari (Lavelle, Kari. Butt or face?, 2025)
"Are you ready for round three of the hilarious guessing game picture book? Discover fascinating facts about disgusting animals while guessing if you're looking at a butt or a face! This picture book continues the entertaining challenge with a new set of (nasty!) animals from all over the world. Examine a close-up photo of an animal and then guess whether you're looking at the top or the...um...bottom. The answer is revealed on the next page with a photo of the complete animal. Readers will discover animals like a horned lizard that shoots blood from its eyes, a tongue-eating louse, a caterpillar that ejects poop, and many more gross, amazing animals. Fun animal facts and information about camouflage and other sneaky animal tricks are included"--